Pengaruh Hubungan antara Setting Pengguna Trotoar terhadap Atribut Aksesibilitas di Kota Semarang pada Era 4.0 Studi Kasus: Trotoar dan Bahu Jalan Setia Budi Semarang - Muhammad Fahri; Helfa Rahmadyani (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2022)
The industrial revolution 4.0 development affects various aspects, such as online transportation which can offerred people to get easy access to everywhere. Along with its rapid development, the presence of online transportation has now become a factor that causes congestion. This is indicated by the large number of online transportation drivers who park along the sidewalks. The relationship between space and activities is called setting. Individual perception of sidewalk user setting is important in assessing environmental attributes, especially the accessibility attributes on the sidewalk. This study aims to find the relationship between sidewalk user settings and accessibility attributes. This study uses qualitative research and an exploratory approach with a person-centered mapping method. The case study is in the Transmart and KFC area, Setia Budi Street, Semarang City. The results of the study reveal that the accessibility attribute settings are highly dependent on the user's point of view. Then the achievement of the effectiveness of the accessibility attribute on the sidewalk is the effectiveness of time. One indicator that has the potential to abuse sidewalks is the cost indicator. Through the person-centered mapping method, the most significant movement scheme occurred on online transportation drivers because of the massive quantity and tend to pile up in one place.